Evidence supporting oxidative stress in a moderately affected area of the brain in Alzheimer’s disease - Youssef, Priscilla; Chami, Belal; Lim, Julia; Middleton, Terry; Sutherland, Greg T.; Witting, Paul K. (Scientific reports, 2018)
The pathogenesis of Alzheimer’s disease (AD) remains to be elucidated. Oxidative damage and excessive beta-amyloid oligomers are components of disease progression but it is unclear how these factors are temporally related. At post mortem, the superior temporal gyrus (STG) of AD cases contains plaques, but displays few tangles and only moderate neuronal loss. The STG at post mortem may represent a brain region that is in the early stages of AD or alternately a region resistant to AD pathogenesis. We evaluated expression profiles and activity of endogenous anti-oxidants, oxidative damage and caspase activity in the STG of apolipoprotein ε4-matched human AD cases and controls. Total superoxide dismutase (SOD) activity was increased, whereas total glutathione peroxidase (GPX), catalase (CAT) and peroxiredoxin (Prx) activities, were decreased in the AD-STG, suggesting that hydrogen peroxide accumulates in this brain region. Transcripts of the transcription factor NFE2L2 and inducible HMOX1 , were also increased in the AD-STG, and this corresponded to increased Nuclear factor erythroid 2-related factor (NRF-2) and total heme-oxygenase (HO) activity. The protein oxidation marker 4-hydroxynonenal (4-HNE), remained unchanged in the AD-STG. Similarly, caspase activity was unaltered, suggesting that subtle redox imbalances in early to moderate stages of AD do not impact STG viability.